2016
DOI: 10.1038/srep28050
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis Strategy for Metal-Organic Frameworks: Dry-Gel Synthesis of MOF-74 Framework with High Yield and Improved Performance

Abstract: Vapor-assisted dry-gel synthesis of the metal-organic framework-74 (MOF-74) structure, specifically Ni-MOF-74 produced from synthetic precursors using an organic-water hybrid solvent system, showed a very high yield (>90% with respect to 2,5-dihydroxyterepthalic acid) and enhanced performance. The Ni-MOF-74 obtained showed improved sorption characteristics towards CO2 and the refrigerant fluorocarbon dichlorodifluoromethane. Unlike conventional synthesis, which takes 72 hours using the tetrahydrofuran-water sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 43 publications
2
41
0
1
Order By: Relevance
“…Several methods have been exploited to synthesize all kinds of MOFs 110 , 111 ( Fig. 4 ) for drug delivery, such as non-solvothermal synthesis, including direct precipitation and vapor diffusion synthesis 91 , and solvothermal methods, microwave-assisted solvothermal synthesis 112 , 113 , synthesis by reverse-phase microemulsions 114 , 115 , 116 , electrochemical synthesis 117 , dry-gel conversion methods 118 , preparation using a microfluidics device 119 , mechanochemical 120 , 121 , 122 or sonochemical synthesis 123 , step-by-step synthesis 124 and high-throughput synthesis methods 125 . The advantages and disadvantages of various synthesis methods are summarized in Table 3 .…”
Section: Synthesis Of Mofsmentioning
confidence: 99%
“…Several methods have been exploited to synthesize all kinds of MOFs 110 , 111 ( Fig. 4 ) for drug delivery, such as non-solvothermal synthesis, including direct precipitation and vapor diffusion synthesis 91 , and solvothermal methods, microwave-assisted solvothermal synthesis 112 , 113 , synthesis by reverse-phase microemulsions 114 , 115 , 116 , electrochemical synthesis 117 , dry-gel conversion methods 118 , preparation using a microfluidics device 119 , mechanochemical 120 , 121 , 122 or sonochemical synthesis 123 , step-by-step synthesis 124 and high-throughput synthesis methods 125 . The advantages and disadvantages of various synthesis methods are summarized in Table 3 .…”
Section: Synthesis Of Mofsmentioning
confidence: 99%
“…Furthermore, since MOFs are also relatively simple to prepare, building components can be well designed which can result in the production of targeted products . Computational calculations have proven to be useful in predictions of interactions between guest hosts and the framework leading to possible synthesis routes for MOFs with required properties .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that MOFs can be synthesized through solvothermal/hydrothermal [14,16], microwave-assisted [17][18][19], sonochemical [20,21], electrochemical [22][23][24], mechanochemical [25,26], ionothermal [27,28], dry gel conversion [29,30], and microfluidic synthesis methods [31,32]. However, the solvothermal technique is the most commonly used method in the synthesis of HKUST-1.…”
Section: Introductionmentioning
confidence: 99%